A chromosomal microarray analysis-based laboratory algorithm for the detection of genetic etiology of early pregnancy loss - Liao, Na; Zhang, Zhu; Liu, Xijing; Wang, Jiamin; Hu, Rui; Xiao, Like; Yang, Yunyuan; Lai, Yi; Zhu, Hongmei; Li, Lingping; Liu, Shanling; Wang, He; et al. (Frontiers in Genetics, 2023)
Background: Chromosomal abnormalities are a major cause of early pregnancy loss.However, models synthesizing existing genetic technologies to improve pregnancy outcomes are lacking. We aim to provide an integrated laboratory algorithm for the genetic etiology of couples who experienced pregnancy loss.Methods: Over a 6-year period, 3,634 products of conception (POCs) following early pregnancy loss were collected. The clinical outcomes from a laboratory algorithm based on single nucleotide polymorphism array (SNP array), fluorescence in situ hybridization (FISH), and parental chromosomal karyotyping assays was comprehensive evaluated.Results: In total, 3,445 of 3,634 (94.8%) POCs had no maternal-cell contamination.Of those POCs, the detection rate of abnormal results was 65.2% (2,247/3,445), of which 91.2% (2,050/2,247) had numerical chromosomal abnormalities, 2.7% (60/2,247) had copy-number variations (CNVs) ≥10 Mb, 2.7% (61/2,247)) had CNVs of terminal deletion and duplication, 2.8% (62/2,247)) had CNVs <10 Mb, and 0.6% (14/2,247)) had uniparental disomy. Furthermore, FISH confirmed 7 of the 60 POCs with mosaic aneuploids below 30% based on the SNP array results as tetraploid. Of the 52 POCs with CNVs of terminal deletion and duplication, 29 couples had balanced rearrangements based on chromosomal karyotyping.The integrated SNP array-based algorithm combined with optional FISH and parental chromosomal karyotyping is an effective laboratory testing strategy, providing a comprehensive and reliable genetic investigation for the etiology of miscarriage, regardless of the number of miscarriages and the method of conception.